2010
DOI: 10.4103/0974-1208.63116
|View full text |Cite
|
Sign up to set email alerts
|

Does local endometrial injury in the nontransfer cycle improve the IVF-ET outcome in the subsequent cycle in patients with previous unsuccessful IVF? A randomized controlled pilot study

Abstract: BACKGROUND:Management of repeated implantation failure despite transfer of good-quality embryos still remains a dilemma for ART specialists. Scrapping of endometrium in the nontransfer cycle has been shown to improve the pregnancy rate in the subsequent IVF/ET cycle in recent studies.AIM:The objective of this randomized controlled trial (RCT) was to determine whether endometrial injury caused by Pipelle sampling in the nontransfer cycle could improve the probability of pregnancy in the subsequent IVF cycle in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(165 citation statements)
references
References 11 publications
4
152
1
8
Order By: Relevance
“…Narvekar et al has demonstrated that the live birth rates, clinical pregnancy and implantation rates significantly increased after endometrial scraping in the preceding cycle in patients with good-quality embryos. 5 The exact mechanism for such effect is not fully understood. However, it is postulated that biopsy/scratching induces an inflammatory response that elevated proinflamatory cytokines, as well as increased MIP-1B expression in the regenerative endometrium, this could play a significant role in implantation process.…”
Section: Discussionmentioning
confidence: 99%
“…Narvekar et al has demonstrated that the live birth rates, clinical pregnancy and implantation rates significantly increased after endometrial scraping in the preceding cycle in patients with good-quality embryos. 5 The exact mechanism for such effect is not fully understood. However, it is postulated that biopsy/scratching induces an inflammatory response that elevated proinflamatory cytokines, as well as increased MIP-1B expression in the regenerative endometrium, this could play a significant role in implantation process.…”
Section: Discussionmentioning
confidence: 99%
“…After that, many trials were performed on women with recurrent implantation failure. Most of these trials showed significant implantation rates improvement on doing the endometrial injury in the preceding cycle [2] [9] [10], while another trial showed no benefit of such a scratching procedure [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hatching, opposition, adherence, penetration and finally invasion are the steps needed for the blastocyst for successful implantation to happen. And the endometrium should be also prepared by estrogen and progesterone and needs to be in time [2]. Barash …”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have suggested that patients with RIF may benefit from endometrial stimulation induced by local injury resulting from a uterine endometrial biopsy catheter in the cycle that precedes the actual treatment cycle [9,58,66,80]. In a randomized controlled trial that included 100 patients with a diagnosis of RIF, Narvekar et al [66] performed two endometrial samplings, one in the follicular phase and the other in the luteal phase of the cycle, antecedent to the embryo transfer cycle.…”
Section: The Endometriummentioning
confidence: 99%
“…In a randomized controlled trial that included 100 patients with a diagnosis of RIF, Narvekar et al [66] performed two endometrial samplings, one in the follicular phase and the other in the luteal phase of the cycle, antecedent to the embryo transfer cycle. The authors reported significant improvement in the clinical pregnancy rate (32.7 % vs13.7 %), the live birth rate (22.4 % vs 9.8 %) and the implantation rate (13.07 % vs 7.1 %) in patients who underwent the intervention as compared to those who did not.…”
Section: The Endometriummentioning
confidence: 99%